Plasma miR‐21 is a novel diagnostic biomarker for biliary tract cancer - Kishimoto, Tomoya (Cancer Sci, 2013)
Biliary tract cancer (BTC) has a generally poor prognosis. Furthermore, it is difficult to distinguish BTC from benign biliary disease (BBD) with commonly used modalities. Therefore, a novel biomarker to facilitate cancer detection is highly desirable. Recent studies have reported the use of circulating microRNAs (miRNAs) as biomarkers for cancers. The purpose of this study was to evaluate whether circulating miRNA‐21 (miR‐21) could be used as a biomarker for BTC. Plasma samples were obtained from 94 BTC patients, 50 healthy volunteers (HVs), and 23 BBD patients. miR‐21 levels in the samples were measured by qRT‐PCR. Plasma miR‐21 levels in patients with BTC were significantly higher than in HVs or in patients with BBD (P < 0.0001 for both). Receiver–operator curve (ROC) curve analysis in differentiating BTC patients from HVs indicated that area under the curve (AUC), optimal sensitivity and specificity was 0.93, 85.1% and 100%, respectively, and those in differentiating BTC patients from BBD patients was 0.83, 72.3%, 91.3%, respectively. Validation of these results indicated that the negative predictive value, positive predictive value, sensitivity, specificity, and accuracy in differentiating BTC patients from HVs was 76.6%, 98.6%, 84.0%, 98.0%, and 88.9%, respectively, and those in differentiating BTC patients from BBD patients was 42.2%, 93.0%, 71.2%, 82.6%, and 72.6%, respectively. These sets of values were improved by combining miR‐21 and CA19‐9 measurements. Plasma miR‐21 is a novel diagnostic biomarker for BTC, and may be useful in distinguishing between BTC and BBD patients.